Better potato for a better life: Reducing food insecurity and dependence on cereals in Amhara Oromia, Tigray and SNNP regions of Ethiopia - Miethbauer, Thomas; Aragaw, A.; Woldegiorgis, G. (International Potato Center, 2015)
This flyer outlines the work done to achieve the goal of enhanced rural incomes, food security and nutrition in four regions of Ethiopia through resilient and profitable potato and sweetpotato value chains. It describes the successes of the first phase of the project (2010-2014) which led to the implementation of the second phase (2015-2016), as well as the progress made between June 2014 and July 2015 in implementing activities that are geared towards increasing access to quality disease-free seed, increasing productivity and revenue, and dietary diversity.